A chest tube translocating the posterior mediastinum: A strange case of malpositioning without complication or injury. (2018) - Almas, E.T.; Gartman, E.; Casserly, B.
Abstract: Malpositioning of a chest tube is a recognised complication of chest tube insertion. However, cases involving the mediastinum comprise only a fraction of such occurrences, while the complete translocation of the tube through the medisastinum is only noted in three published cases. This case report describes a case of complete translocation of the mediastinum during chest tube insertion to resolve a pneumothorax. It examines the possibility of an occult natural pathway in the posterior mediastinum of some patients based on the ease at which the tube crossed the mediastinum, the immediate resolution of patient symptoms and the absence of injury or complications from the event to the patient.